Grouper Imotilization Technique Epinephelus sp. Using Datura Metel L. Seed Extract - Anggi Saputra; Marwita Sari Putri; Azwin Apriandi (Journal of Marine and Coastal Science, 2021)
This study is about fish anesthesia using natural anesthetic ingredients. Natural anesthetic ingredients aim to reduce metabolism in Epinephelus sp. grouper fish. The immobilization method can be used to minimize high metabolism in Epinephelus sp. grouper fish. The purpose of this study was to obtain the influence of Datura metel L. seed extract on the onset time, recovery time, and live graduation of grouper fish Epinephelus sp. The results of the study, using extracts of natural anesthetic ingredients Datura metel L.seed with concentrations of 25%, 30%, and 35% can be concluded that it has a different influence (P<0.05) on the onset and recovered grouper fish. This study gave a life graduation rate of 100% in each concentration. The best concentration in this study was 35% concentration, with the fastest onset time of 3 minutes with a recovery time of 10.67 minutes. This study used a non-Factorial Complete Randomized Design